Upaya Dalam Mempertahankan Kinerja yang Produktif Pada UMKM Goks, Padang - Azizah Latifa; Chairunnisa Charomah; Dasril Dasril; Fadjar Adhiyaksa; Vivi Nila Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Micro, Small and Medium Enterprises (MSMEs) are business activities that are able to expand employment opportunities, provide broad economic services to the community, play a role in the process of equalizing and increasing community income, encourage economic growth, and play a role in realizing national stability. MSMEs are very important in implementing and maintaining productive and healthy performance. One of those who need an adaptation plan is MSME Goks which is located on Jl. Aru No. 13, Lubuk Begalung Nan XX, Padang City, West Sumatra, 25221. Goks is an ice cream business that offers attractive promotions and has a very affordable price factor. This community service activity begins with surveys and interviews, mapping and identifying problems, formulating solutions, and implementing mentoring activities. The impact of this activity is the expansion of product marketing and business development of Goks Padang MSME actors.